Nonlinear Fracture of Functionally Graded Beams under Mode II Loading Conditions - Rizov, V.I. (Проблемы прочности, 2016)
A theoretical study of Mode II fracture in functionally graded beams was carried out. A beam configuration with two symmetric longitudinal cracks was suggested in order to generate Mode II loading conditions. The beam mechanical behavior was described by nonlinear stress–strain relation. The fracture behavior was analyzed by applying the J-integral approach. Closed form analytical solutions were derived of the J-integral for two laws for variation of the modulus of elasticity along the beam height. Nonlinear analyses of the strain energy release rate were performed by considering the energy balance in order to verify the J-integral solutions. The results obtained can be applied to optimize the functionally graded beam structure with respect to the Mode II fracture performance. Also, the analytical solutions derived are very convenient for parametric studies of nonlinear fracture behavior of functionally graded beams. The present paper contributes towards the development of nonlinear fracture mechanics of functionally graded materials. Теоретически изучено разрушение функционально-градиентных балок по моде II. Предложена конфигурация балки с двумя симметричными продольными трещинами для условий нагружения по моде II. Механическое поведение балки описано с помощью нелинейного соотношения между напряжением и деформацией. Процесс разрушения проанализирован на основе применения J-интеграла. Получено аналитическое решение на основе J-интеграла для двух законов изменения модуля упругости по высоте балки. Выполнен нелинейный анализ скорости высвобождения энергии деформации с учетом баланса энергии для проверки решений на основе J-интеграла. Полученные результаты могут быть использованы для оптимизации функционально-градиентной структуры балки при разрушении по моде II. Аналитические решения удобны также для параметрического изучения нелинейного разрушения функционально-градиентных балок, что дает возможность в дальнейшем развивать нелинейную механику разрушения функционально-градиентных материалов. Теоретично вивчено руйнування функціонально-градієнтних балок по моді ІІ. Запропоновано конфігурацію балки з двома симетричними поздовжніми тріщинами для умов навантаження по моді ІІ. Механічну поведінку балки описано за допомогою нелінійного співвідношення між напруженням і деформацією. Процес руйнування проаналізовано на основі використання J-інтеграла. Отримано аналітичний розв'язок на основі J-інтеграла для двох законів зміни модуля пружності по висоті балки. Виконано нелінійний аналіз швидкості звільнення енергії деформації з урахуванням балансу енергії для перевірки розв'язків на основі J-інтеграла. Отримані результати можуть бути використані для оптимізації функціонально-градієнтної структури балки при руйнуванні по моді ІІ. Аналітичні розв'язки зручні для параметричного вивчення нелінійного руйнування функціонально-градієнтних балок, що дає підстави для подальшого розвитку нелінійної механіки руйнування функціонально-градієнтних матеріалів.